Physical Condition as a Contribution of Shooting Accuracy with Flick Drag Technique (Department of Physical Education, Sport, Health and Recreation, 2018)
The purpose of this study was to examine how much the contribution of grip strength, arm muscle power, flexibility togok, and eye and hand coordination to shooting accuracy with drag flick technique. This research uses correlational method. A total of 40 men’s hockey players were selected as samples in this study. The data analysis technique used multiple regression and coefficient determination test (R2). It can be concluded that the grip strength variable, arm muscle power, togok flexibility, and eye and hand coordination have an effect on shooting accuracy with drag flick technique and produce significant contribution. Relationship with Flick Drag shot accuracy was power muscle arm with a result of 34.6%, then body flexibility of 20.5%, holding strength of 17.9%, and the least contribution of hand-eye coordination of 14.3%.